Antiphospholipid antibodies in patients with COVID‐19: A relevant observation?. (23rd July 2020) - Devreese, Katrien M. J.; Linskens, Eleni A.; Benoit, Dominique; Peperstraete, Harlinde
Abstract: Background: High incidence of thrombosis in COVID‐19 patients indicates a hypercoagulable state. Hence, exploring the involvement of antiphospholipid antibodies (aPL) in these patients is of interest. Objectives: To illustrate the incidence of criteria (lupus anticoagulant [LAC], anticardiolipin [aCL] immunoglobulin G [IgG]/IgM, antibeta2‐glycoprotein I antibodies [aβ2GPI] IgG/IgM) and noncriteria (anti‐phosphatidyl serine/prothrombin [aPS/PT], aCL, and aβ2GPI IgA) aPL in a consecutive cohort of critically ill SARS‐CoV‐2 patients, their association with thrombosis, antibody profile and titers of aPL. Patients/Methods: Thirty‐one consecutive confirmed COVID‐19 patients admitted to the intensive care unit were included. aPL were measured at one time point, with part of the aPL‐positive patients retested after 1 month. Results: Sixteen patients were single LAC‐positive, two triple‐positive, one double‐positive, one single aCL, and three aCL IgG and LAC positive. Seven of nine thrombotic patients had at least one aPL. Sixteen of 22 patients without thrombosis were aPL positive, amongst them two triple positives. Nine of 10 retested LAC‐positive patients were negative on a second occasion, as well as the double‐positive patient. Seven patients were aPS/PT‐positive associated to LAC. Three patients were aCL and aβ2GPI IgA‐positive. Conclusion: Our observations support the frequent single LAC positivity during (acute phase) observed in COVID‐19 infection; however, not clearly related to thrombotic complications. Triple aPL positivity and high aCL/aβ2GPI titers are rare. Repeat testing suggests aPL to be mostly transient. Further studies and international registration of aPL should improve understanding the role of aPL in thrombotic COVID‐19 patients.